Unveiling the Beauty of Figurative Language: A Stylistic Analysis of Qur’an Surah As-Saffat and Ar-Rahman in Abdullah Yusuf Ali’s Translation - Dipta, Dinar; binti Haji Abd Karim, Norhayati; Virgiyanti, Diska Fatima; Nuraini, Eka Indah; Fachriza, Aries; Aniesa (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: Figurative language deals with non-literal language to shift meaning by comparing other words to the original composition. This appears in many works of literature, including the holy Qur’an. Therefore, it is essential to study, not intending to reduce or increase the meaning of the Qur’an. Aims: This study aims to identify the types of figurative language in the surahs As-Saffat and Ar-Rahman and examine the most dominant figurative language in both surahs. Methods: This qualitative study analyzed the linguistic phenomena in the verses. The objects were As-Saffat, which consists of 182 verses, and surah Ar-Rahman, which consists of 78 verses. The data were presented descriptively. Results: The findings revealed that 81 verses in both Surah As-Saffat and Ar-Rahman contain figurative language. Surah As-Saffat contained 32 data points of figurative language, while Ar-Rahman had 49 data points. The most dominant type of figurative language in Surah As-Saffat is ellipsis, and in Surah Ar-Rahman, it is rhetoric. Implications: The analysis results reflect that academics can be a form of integration between religious and general science, such as literature. Therefore, a more in-depth al-Qur’an can be easily perceived. Although related to general science, it does not leave the rules in interpreting the Qur’an. This can enrich the reference for Teaching English as a Foreign Language.